Prevalence Rate of Rheumatoid Arthritis among Patients Attending Rheumatology Consultation Clinic at Baquba Teaching Hospital - Kadhim Rashid , Muayad (Diyala Journal of Medicine, 2023)
Background: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that causes progressive and painful of multiple joints damage. Objective: To explore the prevalence of Rheumatoid arthritis (RA) among middle-aged and older of Iraqi patients attended the outpatients’ clinics. Patients and Methods: A prospective cross-sectional study was conducted from 1st February to 31st July 2022 at the rheumatology outpatient clinic at the Baquba teaching hospitals, Diyala province, Iraq. The eligible patients were interviewed using semi-structured questionnaires. Diagnosis of RA is based on clinical and serological parameters in accordance with criteria issued by American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) guideline. Descriptive, bivariate, and logistic regression analysis was performed. All statistical analyses were performed using SPSS 16.0 software. P-value < 0.05 was considered statistically significant. Results: A total of 417 patients with an average age of 55.05 (+10.31) (ranged 40-79 years) have been included in the study. More than half were females (57.8%), married (74.3%), unemployed (67.9%), and 41.0% doctor-diagnosed arthritis. The prevalence of RA in adults was 0.96% compared to 2.34% in doctor-diagnosed arthritis group (females 1.75% vs. males 0.59%, P= 0.011). Results of the multiple logistic regressions showed that older age (odds ratio (OR) = 1.100, 95% CI: 1.070 to 1.130) was associated significantly with "doctor-diagnosed arthritis" (p < 0.001). The female patients (OR = 4.928, 95% CI: 2.826 to 8.593), single or had no spouse (unmarried, widow, divorce) (OR = 5.076, 95% CI: 2.742 to 9.396) and had diabetes mellitus (DM) (OR = 7.251, 95% CI: 4.247 to 12.378) were associated significantly with "doctor-diagnosed arthritis" (p < 0.001). Conclusion: With aging, the Iraqi females who have no spouse and suffer from diabetes mellitus become more vulnerable to symptomatic arthritis.